Tumor‐associated antigens: Tn antigen, sTn antigen, and T antigen. (28th September 2016) - Fu, C.; Zhao, H.; Wang, Y.; Cai, H.; Xiao, Y.; Zeng, Y.; Chen, H.
Abstract: Glycosylation is one of the major posttranslational modifications of proteins. N‐glycosylation (Asn‐linked) and O‐glycosylation (Ser/Thr‐linked) are the two main forms. Abnormal O‐glycosylation is frequently observed on the surface of tumor cells, and is associated with an adverse outcome and poor prognosis in patients with cancer. O‐glycans (Tn, sTn, and T antigen) can be synthesized in the Golgi apparatus with the aid of several glycosyltransferases (such as T‐synthase and ST6GalNAc‐I) in a suitable environment. The unique molecular chaperone of T‐synthase is Cosmc, which helps T‐synthase to fold correctly in the endoplasmic reticulum. Dysregulation of these glycosyltransferases, molecular chaperones, or the environment is involved in the dysregulation of O‐glycans. Tn, sTn, and T antigen neo‐ or over‐expression occurs in many types of cancer including gastric, colon, breast, lung, esophageal, prostate, and endometrial cancer. This review discusses the major synthetic pathway of O‐glycans and the mechanism by which Tn, sTn, and T antigens promote tumor metastasis.